Restoration of Extension of the Great Toe After an Untreated, Retracted Extensor Hallucis Longus Rupture: A Case Report. Issue 4 (October 2019) - Jaffe, David
Abstract : Case: A 66-year-old woman presented 10 days after dropping a knife onto her right foot. She was diagnosed with a complete, retracted extensor hallucis longus (EHL) rupture. A recommendation for acute repair was made, but she opted against surgery and was treated with observation and supportive care. At 1 year, the patient regained active extension of her big toe and had no gait disturbances or functional impairment. Conclusions: There is no literature on the natural history of a retracted EHL rupture. Surgery is typically advised to prevent symptomatic drop toe and theoretical subsequent deformity. This case illustrates the potential for restoration of extension of the hallux without surgical repair.